Upaya Meningkatkan Pemahaman tentang Kegiatan Ekonomi dan Pekerjaan menggunakan Model Pembelajaran Think Pair Share (TPS) pada siswa Kelas IVA SDN Tanahwulan 1 Kecamatan Maesan Kabupaten Bondowoso - Yayuk Susilawati (STKIP PGRI SITUBONDO, 2023)
Low understanding of economic activities and work in grade IVa students is the focus of research. This is reinforced by observational data conducted by researchers related to the understanding of economic and work activities that are very concerning, from 22 students observed, only 45% or 10 students obtained scores above the minimum completeness criteria set at 63, with the results of assessing student activities during classroom learning on average 47% with poor criteria. The results of the study can be concluded that the use of the Think Pair Share (TPS) learning model can increase students' understanding of economic activities and work. This can be seen from the results of the analysis of each indicator in this study increased sharply from the initial condition to the final stage of action. This increase in social studies understanding of economic and work activity material is marked by an increase in learning completeness in cycle 1 obtained above KKM by 66% and in cycle 2 by 100%, with the average value of student evaluation in cycle 1 of 73, while in cycle 2 of 85